2011
DOI: 10.1111/j.1468-2494.2011.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent changes in eumelanin composition in hairs of various ethnic origins

Abstract: SynopsisHair pigmentation is one of the most conspicuous phenotypes of humans. From a chemical point of view, however, data remain scarce regarding human hair pigmentation characteristics. To determine melanin content and composition in human eumelanic hair from individuals of different ethnic origins and at different ages, we collected hair from 56 subjects with eumelanic hair from each group of African-American, East Asian, and Caucasian origin. The 56 subjects consist of 14, seven each of males and females,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…DCT expression has been proposed to affect age-dependent changes in eumelanin composition in hairs between African, European, and Asian populations [130]. Lao et al [37] showed a haplotype of DCT locus being highly frequent in Han Chinese (75%) but absent in the European and the African populations, suggestive for positive selection on DCT in East Asians as also confirmed by later studies [131,132].…”
Section: Tyr Tyrp1 and Dctmentioning
confidence: 81%
“…DCT expression has been proposed to affect age-dependent changes in eumelanin composition in hairs between African, European, and Asian populations [130]. Lao et al [37] showed a haplotype of DCT locus being highly frequent in Han Chinese (75%) but absent in the European and the African populations, suggestive for positive selection on DCT in East Asians as also confirmed by later studies [131,132].…”
Section: Tyr Tyrp1 and Dctmentioning
confidence: 81%
“…This was determined by direct measurement of melanin content and type of eumelanin in a sample of African-American, East Asian and Caucasian individuals [85]. African and European hairs were found to have changes in the ratio of dihydroxyindole (DHI) to 5,6-dihydroxyindole-2-carboxylic acid (DHICA), favoring DHI more as people age.…”
Section: Human Pigmentation Genes With Signs Of Selection Pressurementioning
confidence: 99%
“…African and European hairs were found to have changes in the ratio of dihydroxyindole (DHI) to 5,6-dihydroxyindole-2-carboxylic acid (DHICA), favoring DHI more as people age. However, the Asian samples seemed to have low DHICA levels throughout life, and did not have graying to the extent of other populations [85]. Since a major role of dopachrome tautomerase (DCT) is the isomerization of dopachrome to DHICA, it is plausible that these ethnic differences reflect differences in DCT expression.…”
Section: Human Pigmentation Genes With Signs Of Selection Pressurementioning
confidence: 99%
“…Thus, melanic hues may result from a combination of variation in absolute and relative concentration of either melanin [26][28]. Moreover, ontogenetic variation can occur, with an age-related change in absolute as well as relative production of either melanin form [29], [30].…”
Section: Introductionmentioning
confidence: 99%